Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0081035
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Structure to Protein-Protein Interaction Networks That Drive Metastasis to Brain and Lung in Breast Cancer

Abstract: Blocking specific protein interactions can lead to human diseases. Accordingly, protein interactions and the structural knowledge on interacting surfaces of proteins (interfaces) have an important role in predicting the genotype-phenotype relationship. We have built the phenotype specific sub-networks of protein-protein interactions (PPIs) involving the relevant genes responsible for lung and brain metastasis from primary tumor in breast cancer. First, we selected the PPIs most relevant to metastasis causing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…BLAST scores were used as the edge metric for full sequence‐based networks, and TM‐Align scores as the edge metric for structure‐based networks. Both of these methods have previously been used as metrics for sequence and structural comparison, respectively. For active site comparison, we used active site profiling, a method previously developed to identify and quantitatively compare active site microenvironments .…”
Section: Introductionmentioning
confidence: 99%
“…BLAST scores were used as the edge metric for full sequence‐based networks, and TM‐Align scores as the edge metric for structure‐based networks. Both of these methods have previously been used as metrics for sequence and structural comparison, respectively. For active site comparison, we used active site profiling, a method previously developed to identify and quantitatively compare active site microenvironments .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the well-established notion that a disease, especially cancer, is usually a result of complex interactions and communications within a large set of proteins and other molecules. Such integrative analysis has been applied to study lung cancer (Wu et al 2016), brain cancer (Engin et al 2013), prostate cancer (Chen et al 2016), and non-cancer diseases such as diabetes (Vyas et al 2016) and polycystic ovarian syndrome (PCOS) (Mohamed-Hussein & Harun 2009). In this study, we analysed laryngeal cancer-related protein-protein interaction (PPI) networks to improve our understanding of the complexity of the molecular pathways that underlie laryngeal cancer to identify the dynamic processes involved in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups have published high-resolution three-dimensional (3D) PPI networks [8][9][10] that include the molecular details of binding interfaces. Applications of these to investigate inherited disease mutations [11][12][13][14][15] have suggested that a) nsSNVs located at protein interfaces result in distinct phenotypes from those located in the protein core 9,10 , b) known disease associated variants outside of the core are enriched at residues participating in protein interaction interfaces 10 c) in particular, in-frame disease mutations are enriched at interface regions of interacting proteins 9 and d) disease mutations at distinct interfaces of the same protein can be associated with distinct disease phenotypes 9 . In cancer, 3D location of mutations at an interface has served as evidence that protein interactions may be important for metastasis site determination.…”
Section: Introductionmentioning
confidence: 99%